Microvasculatures: Multiphoton‐Guided Creation of Complex Organ‐Specific Microvasculature (Adv. Healthcare Mater. 10/2021). Issue 10 (19th May 2021) - Rayner, Samuel G.; Howard, Caitlin C.; Mandrycky, Christian J.; Stamenkovic, Stefan; Himmelfarb, Jonathan; Shih, Andy Y.; Zheng, Ying
Abstract : Engineering functional tissues for regenerative medicine and human disease modeling is limited by difficulty re‐creating in vivo‐like microvasculatures. In article number 2100031, Ying Zheng and co‐workers report the successful combination of multiphoton microscopy with directed angiogenesis to precisely generate perfusable 3D organ‐specific capillary beds within natural extracellular matrices. These methods enable full cellularization of complex capillary models and the creation of multicellular, heterogeneous, and hierarchical vasculatures.